The role of the media against computer fraud. Dissemination, prevention and literacy - Mendoza Michilot, María (2025)
Computer fraud is a crime that increased in the context of the Covid-19 pandemic in the world, and Peru was no exception. Therefore, we were interested in gathering Peruvians’ perspectives on the use of the press and social media in the dissemination and, eventually, their participation in a digital financial literacy strategy, as a preventive measure to avoid further losses from this crime. A survey of 429 residents in Metropolitan Lima and interviews with 25 victims of computer fraud revealed that Facebook and conventional television are the platforms most used to learn about the modus operandi of crime; that the majority do not share their experiences in the media because they distrust them or perceive that they do not contribute to clarifying their complaints. The study proposes a minimum informative strategy that the press could consider in its daily work, to guide people on how to prevent, denounce and find a solution; to avoid the impunity of crime and, at the same time, to build citizenship.